Learning and performing political violence: ZANU-PF Youth and the 2008 presidential run-off election in Zimbabwe. Issue 4 (1st October 2020) - Mwonzora, Gift; Helliker, Kirk
ABSTRACT: This article examines political violence enacted by youth during the presidential run-off election in Zimbabwe in 2008. After the presidential election in March 2008, no clear winner emerged, leading to a run-off election in June 2008 between Robert Mugabe of Zimbabwe African National Union-Patriotic Front (ZANU-PF) and Morgan Tsvangirai of the Movement for Democratic Change (MDC). In the face of a possible defeat in the run-off, ZANU-PF unleashed significant levels of violence against MDC activists and members, such that Tsvangirai withdrew. Central to the violence were youths, and mainly young men, who performed this violence for diverse reasons, including promises of material rewards and compliance due to fear of being labelled as a sell-out. While not denying the significance of these reasons, this article explores the importance of political socialisation of youth in Zimbabwe by the 'war generation', that is, those who fought during the war of liberation in the 1970s. This socialisation entailed the propagation of an authoritarian nationalist narrative by ZANU-PF in which violence was justified in defending 'the revolution'. This narrative was very pervasive in the years preceding 2008 and in the months leading up to the run-off. There is evidence that suggests that youths learnt about the efficacy of violence through this process of political socialisation and, on this basis, performed violence during the run-off. We conclude that this 'indoctrination' is of some significance in understanding youth violence in 2008. However, we argue that any youths considered as inspired on nationalist grounds to enact violence also had their own personal motivations that are irreducible to nationalist fervour.